Method for preparing superabsorbent polymer
By polymerizing and adding carboxylic acid additives of specific structures in the presence of an encapsulated foaming agent, the problem that superabsorbent polymers are difficult to maintain permeability and prevent agglomeration at high absorption rates is solved, and efficient permeability and anti-caking efficiency are achieved.
Patent Information
- Application Number
- CN202180022276.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-08
- Filing Date
- 2021-11-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-11-10
AI Technical Summary
The existing superabsorbent polymers have difficulty maintaining good permeability and preventing agglomeration while having high absorption rates, especially under external pressures.
Superabsorbent polymers with improved permeability and anti-caking efficiency were prepared by polymerizing the monomer in the presence of an encapsulated foaming agent and adding carboxylic acid additives with specific structures to the hydrogel polymer, and then coarse pulverization.
The permeability and anti-caking efficiency of superabsorbent polymers are achieved without reducing the absorption rate, and the defect of degradation of absorption performance when using inorganic materials is avoided.
Smart Images

Figure FHA0000010191390000011 
Figure FHA0000010191390000021 
Figure FHA0000010191390000022
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0162891 filed in the Korean Intellectual Property Office on November 27, 2020, and Korean Patent Application No. 10-2021-0152461 filed in the Korean Intellectual Property Office on November 8, 2021, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present invention relates to a method for preparing a super absorbent polymer. More specifically, the present invention relates to a method for preparing a super absorbent polymer having improved permeability and anti-caking efficiency while having a high absorption rate. Background Art
[0004] Super absorbent polymer (SAP) is a synthetic polymer material that can absorb 500 to 1000 times its own weight in water. Various manufacturers have given it different names, such as SAM (super absorbent material) and AGM (absorbent gel material). This super absorbent polymer has begun to be put into practical use in sanitary products, and is now widely used not only in sanitary products, but also in water-retaining soil products for gardening, water-stopping materials for civil engineering and construction, sheets for seedling cultivation, preservatives in the field of food circulation, materials for hot compresses, etc.
[0005] These superabsorbent polymers have been widely used in the field of sanitary materials, such as diapers or sanitary napkins. In such sanitary materials, superabsorbent polymers are generally contained in a state of being spread in pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with a thinner thickness. As part of these efforts, so-called pulp-free diapers and the like, which reduce the pulp content or do not use pulp at all, are being actively developed.
[0006] As described above, in the case of a sanitary material with reduced pulp content or without using pulp, the content ratio of superabsorbent polymer is high, and these superabsorbent polymer particles are inevitably contained in the sanitary material in a multi-layer form. In order to make the entire superabsorbent polymer particles contained in the multi-layer more effectively absorb a large amount of liquid, such as urine, the superabsorbent polymer needs to have high absorption performance and a fast absorption rate. In addition, the superabsorbent polymer does not release the absorbed liquid even under external pressure, and in addition, it should well maintain the shape even in a state where the volume is expanded (swollen) due to the absorption of liquid, thereby showing excellent permeability.
[0007] Superabsorbent polymers include multiple hydrophilic parts on their surfaces to exhibit high absorption performance for liquids, especially water. Therefore, when exposed to air, superabsorbent polymer particles will aggregate and agglomerate due to absorbing moisture contained in the air.
[0008] Therefore, there has been a need to develop superabsorbent polymers having improved permeability without reducing the absorption rate while preventing the agglomeration phenomenon between superabsorbent polymer particles, in addition to improving the centrifuge retention capacity (CRC) and absorbency under pressure (AUP), which are physical properties indicating the basic absorption capacity and water retention capacity of superabsorbent polymers. Summary of the invention
[0009] Technical issues
[0010] Therefore, the present disclosure relates to a method for preparing a superabsorbent polymer having improved permeability and anti-caking efficiency while having a high absorption rate by polymerizing monomers in the presence of an encapsulated foaming agent and adding an additive having a specific structure to a hydrogel polymer, followed by coarse pulverization.
[0011] Technical Solution
[0012] In order to solve the above problems, a method for preparing a superabsorbent polymer is provided, which comprises:
[0013] A step of forming a hydrogel polymer by crosslinking polymerization of a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups in the presence of an internal crosslinking agent, an encapsulated foaming agent and a polymerization initiator (step 1);
[0014] A step of mixing a hydrogel polymer with a carboxylic acid additive and then coarsely grinding the hydrogel polymer (step 2);
[0015] A step of dry-pulverizing the roughly pulverized hydrogel polymer to prepare a powdery base resin (step 3); and
[0016] a step of further crosslinking the surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer (step 4),
[0017] The carboxylic acid additive is at least one selected from the group consisting of carboxylic acids and salts thereof represented by the following Chemical Formula 1:
[0018] [Chemical formula 1]
[0019]
[0020] In chemical formula 1,
[0021] A is a C5 to C21 alkyl group,
[0022] B 1 is -OCO-, -COO- or -COOCH(R 1 )COO-,
[0023] B 2 Yes-CH 2 -、-CH 2 CH 2 -、-CH(R 2 )-, -CH=CH- or -C≡C-,
[0024] Where R 1 and R 2 are each independently C1 to C4 alkyl,
[0025] n is an integer from 1 to 3, and
[0026] C is a carboxyl group.
[0027] Beneficial Effects
[0028] According to the method for preparing a super absorbent polymer disclosed herein, by adding an additive having a specific structure to a hydrogel polymer polymerized in the presence of an encapsulated foaming agent and then coarsely pulverizing, a super absorbent polymer having improved permeability and anti-caking efficiency without reducing the absorption rate can be prepared. In addition, without adding an inorganic material added in the surface cross-linking step, the permeability and anti-caking efficiency can be improved, thereby preventing the absorption performance from being reduced due to the addition of an inorganic material. DETAILED DESCRIPTION
[0029] The terms used herein are only used to explain specific embodiments and are not intended to limit the present invention. Singular forms are intended to also include plural forms, unless the context clearly indicates otherwise. It will be further understood that when used in this specification, the terms "include", "have" or "have" specify the presence of the features, steps, components or combinations thereof, but do not exclude the presence or addition of one or more other features, steps, components or combinations thereof.
[0030] Since the present invention can be variously modified and have various forms, its specific embodiments are shown by way of example and will be described in detail. However, this is not intended to limit the present invention to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the scope of the thought and technology of the present invention.
[0031] Hereinafter, according to specific embodiments of the present invention, a method for preparing a super absorbent polymer and the super absorbent polymer will be described in more detail.
[0032] The terms are used only to refer to specific embodiments, and are not used to limit the present disclosure unless explicitly expressed. A singular expression of the present disclosure may include a plural expression unless they are expressed differently in context.
[0033] According to an embodiment of the present disclosure, there is provided a method for preparing a superabsorbent polymer, comprising:
[0034] A step of forming a hydrogel polymer by crosslinking polymerization of a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups in the presence of an internal crosslinking agent, an encapsulated foaming agent and a polymerization initiator (step 1);
[0035] A step of mixing a hydrogel polymer with a carboxylic acid additive and then coarsely grinding the hydrogel polymer (step 2);
[0036] A step of dry-pulverizing the roughly pulverized hydrogel polymer to prepare a powdery base resin (step 3); and
[0037] a step of further crosslinking the surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer (step 4),
[0038] The carboxylic acid additive is at least one selected from the group consisting of carboxylic acids and salts thereof represented by the following Chemical Formula 1:
[0039] [Chemical formula 1]
[0040]
[0041] In chemical formula 1,
[0042] A is a C5 to C21 alkyl group,
[0043] B 1 is -OCO-, -COO- or -COOCH(R 1 )COO-,
[0044] B 2 Yes-CH 2 -、-CH 2 CH 2 -、-CH(R 2 )-, -CH=CH- or -C≡C-,
[0045] Where R 1 and R 2 are each independently C1 to C4 alkyl,
[0046] n is an integer from 1 to 3, and
[0047] C is a carboxyl group.
[0048] The term "polymer" in the present disclosure refers to a state in which a water-soluble ethylenically unsaturated monomer is polymerized, and may include all moisture content ranges, or all particle size ranges. Among these polymers, a polymer having a moisture content of about 30% by weight or more after polymerization and before drying may be referred to as a hydrogel polymer, and particles in which the hydrogel polymer is pulverized and dried may be referred to as a cross-linked polymer.
[0049] Furthermore, the term "superabsorbent polymer particles" refers to particulate materials comprising crosslinked polymers in which water-soluble ethylenically unsaturated monomers having at least partially neutralized acidic groups are polymerized and crosslinked by an internal crosslinking agent.
[0050] Furthermore, the term "superabsorbent polymer" is used to encompass all cross-linked polymers in which water-soluble ethylenically unsaturated monomers having at least partially neutralized acidic groups are polymerized, or a base resin in the form of a powder consisting of superabsorbent polymer particles in which the cross-linked polymer is pulverized, and the cross-linked polymer or the base resin is further processed, such as drying, pulverizing, classifying, surface cross-linking, etc., to be in a state suitable for commercialization, as the case may be. Therefore, the term "superabsorbent polymer" can be interpreted as encompassing a composition comprising a superabsorbent polymer, that is, a plurality of superabsorbent polymer particles.
[0051] In addition, the term "general super absorbent polymer particles" refers to particles having a particle diameter of 150 μm to 850 μm among super absorbent polymer particles.
[0052] Furthermore, the term "fine powder" refers to particles having a particle size of less than 150 μm among superabsorbent polymer particles.
[0053] Furthermore, the term "mincing" refers to cutting the hydrogel polymer into small pieces to improve drying efficiency, separate from pulverizing into a common particle size.
[0054] In recent years, in the case of using sanitary materials, especially diapers, how long the dry state of the diaper surface can be maintained has become an important measure for evaluating the characteristics of diapers. Therefore, in addition to improving the water retention capacity, water retention capacity and pressure absorbency, which are the basic physical properties of superabsorbent polymers, improving permeability and preventing the caking phenomenon have become important issues.
[0055] In particular, in the prior art, a method of using an inorganic material such as aluminum sulfate in the surface crosslinking step is adopted to improve the dispersibility of the surface crosslinking liquid, thereby improving the permeability and anti-caking (A / C) efficiency of the superabsorbent polymer finally prepared. However, when such an inorganic material is added, there is a problem that the pressure absorbency of the superabsorbent polymer is reduced.
[0056] Therefore, the present inventors have found that when a carboxylic acid additive having a specific structure is added to a hydrogel polymer before the shredding step of the hydrogel polymer, i.e., before coarse pulverization, and an encapsulated foaming agent is used during the polymerization process, the permeability and anti-caking efficiency of the finally prepared superabsorbent polymer can be improved at the same time without using such an inorganic material, thereby completing the present invention. Therefore, it is possible to prevent the absorption performance from being reduced due to the use of an inorganic material such as aluminum sulfate in the surface cross-linking step.
[0057] Here, the carboxylic acid additive added to the hydrogel polymer before the coarse pulverization is at least one compound selected from the group consisting of carboxylic acids and salts thereof represented by Chemical Formula 1, and has both a hydrophobic functional group and a hydrophilic functional group. At the same time, since the water-soluble ethylenically unsaturated monomer contains an acidic group (-COOH) and / or a neutralized acidic group (-CO - ), and due to the acidic groups (-COOH) and / or neutralized acidic groups (-COO - ) does not participate in the polymerization and remains, so a large amount of hydrophilic parts exist on the surface of the hydrogel polymer prepared by polymerization. Therefore, when the additive is added to the hydrogel polymer, the hydrophilic functional group of the additive is adsorbed to at least a part of the hydrophilic part existing on the surface of the hydrogel polymer, and the polymer surface adsorbed with the additive becomes hydrophobic due to the hydrophobic functional group located at the other end of the additive. Therefore, the hydrogel polymer mixed with the carboxylic acid additive can be easily coarsely pulverized, and the aggregation between the coarsely pulverized hydrogel polymers can also be suppressed.
[0058] More specifically, in the carboxylic acid additive, the hydrophobic functional group is a C5 to C21 alkyl group (A portion), and the hydrophilic functional group is a C portion, specifically a carboxyl group (COOH) or a carboxylate group (-COO in the case of a salt). - The hydrophobic functional group and the hydrophilic functional group are located at both ends of the additive. In particular, the carboxylic acid additive includes (B 1 -B 2 ) part, and (B 1 -B 2 ) part improves the adsorption performance on the polymer surface, which may be insufficient with only part C. Therefore, compared with having an AC structure without (B 1 -B 2 ) part, the additive having the structure of Chemical Formula 1 has excellent adsorption performance on the polymer surface showing hydrophilicity.
[0059] Therefore, since at least some of the additives are also present on the surface of the finally prepared super absorbent polymer particles, even if no additional hydrophobic additive is added to the base resin, aggregation and agglomeration between particles can be prevented, and permeability can also be improved.
[0060] Hereinafter, a method for preparing a super absorbent polymer composition according to an exemplary embodiment will be described in more detail.
[0061] (Step 1)
[0062] The above step is to form a hydrogel polymer by crosslinking polymerization of a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups in the presence of an internal crosslinking agent, an encapsulated foaming agent, and a polymerization initiator. This step may include: a step of preparing a monomer composition by mixing a water-soluble ethylenically unsaturated monomer, an encapsulated foaming agent, an internal crosslinking agent, and a polymerization initiator, and a step of forming a hydrogel polymer by thermally polymerizing or photopolymerizing the monomer composition.
[0063] The water-soluble ethylenically unsaturated monomer can be any monomer commonly used in preparing superabsorbent polymers. As a non-limiting example, the water-soluble ethylenically unsaturated monomer can be a compound represented by the following Chemical Formula 2:
[0064] [Chemical formula 2]
[0065] R-COOM'
[0066] In chemical formula 2,
[0067] R is a C2 to C5 alkyl group having an unsaturated bond, and
[0068] M' is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0069] Preferably, the monomer may be at least one selected from the group consisting of (meth)acrylic acid and monovalent (alkali) metal salts, divalent metal salts, ammonium salts and organic amine salts of the acid.
[0070] When (meth) acrylic acid and / or its salt is used as a water-soluble ethylenically unsaturated monomer, it is advantageous to obtain a superabsorbent polymer having improved absorption properties. In addition, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide, etc. can be used as monomers.
[0071] Here, the water-soluble ethylenically unsaturated monomer may have an acidic group, and at least a portion of the acidic group may be neutralized by a neutralizing agent. Specifically, in the step of mixing the water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, a polymerization initiator, and a neutralizing agent, at least a portion of the acidic group of the water-soluble ethylenically unsaturated monomer may be neutralized. In this case, alkaline substances such as sodium hydroxide, potassium hydroxide, and ammonium hydroxide that can neutralize the acidic group may be used as the neutralizing agent.
[0072] In addition, the degree of neutralization of water-soluble ethylenically unsaturated monomers can be 50 to 90 % by mole, 60 to 85 % by mole, 65 to 85 % by mole or 65 to 75 % by mole, wherein the degree of neutralization refers to the degree to which the acidic groups contained in the water-soluble ethylenically unsaturated monomers are neutralized by the neutralizing agent. The scope of the degree of neutralization can change according to final physical properties. Too high a degree of neutralization causes the precipitation of neutralized monomers, and therefore may not be easy to polymerize. On the contrary, too low a degree of neutralization not only deteriorates the absorbency of polymers, but also gives polymers difficult properties, such as the properties of elastic rubber.
[0073] In addition, the term "internal crosslinking agent" used herein is different from the surface crosslinking agent used for crosslinking the surface of the super absorbent polymer particles described later, and the internal crosslinking agent polymerizes the unsaturated bonds of the water-soluble ethylenically unsaturated monomers by crosslinking. The crosslinking in the above step is performed both on the surface and inside, but when the surface crosslinking step of the super absorbent polymer particles described later is performed, the particle surface of the super absorbent polymer finally prepared has a structure crosslinked by the surface crosslinking agent, and the inside of the particle has a structure crosslinked by the internal crosslinking agent.
[0074] As an internal crosslinking agent, any compound can be used as long as it allows the introduction of crosslinking bonds during the polymerization of water-soluble ethylenically unsaturated monomers. As a non-limiting example, the internal crosslinking agent can be a multifunctional crosslinking agent. For example, it can be an acrylate compound, such as N, N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol Alcohol pentaacrylate, glycerol tri(meth)acrylate and pentaerythritol tetraacrylate; epoxy compounds such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polybutylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether and polyglycerol polyglycidyl ether; triarylamine; propylene glycol; glycerol; or ethylene carbonate, and these can be used alone or in combination of two or more. However, the present disclosure is not limited thereto.
[0075] According to one embodiment, epoxy compounds can be used as internal crosslinking agents. For example, ethylene glycol diglycidyl ether can be used as an internal crosslinking agent, and even in this case, the foaming by the foaming agent can be stably performed by the hydrophobic particles. In addition, acrylate compounds such as polyethylene glycol di(meth)acrylate can be used together with epoxy compounds as internal crosslinking agents.
[0076] The cross-linking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of an internal cross-linking agent can be carried out by thermal polymerization, photopolymerization or mixed polymerization in the presence of a polymerization initiator, with or without a thickener, plasticizer, storage stabilizer, antioxidant, etc., but the specific details are described later.
[0077] In the monomer composition, the usage amount of the internal crosslinking agent can be 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. For example, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer, the usage amount of the internal crosslinking agent can be more than 0.01 parts by weight, more than 0.05 parts by weight, or more than 0.1 parts by weight, and less than 5 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, or less than 0.5 parts by weight. When the internal crosslinking agent used is too little, crosslinking is insufficient, and it is difficult to reach the strength above the appropriate level, and when the internal crosslinking agent used is too much, the internal crosslinking density increases, and therefore it may be difficult to reach the required water retention capacity level.
[0078] In addition, the polymerization initiator can be appropriately selected according to the polymerization method. In the case of thermal polymerization, a thermal polymerization initiator is used, and in the case of photopolymerization, a photopolymerization initiator is used. In addition, in the case of a mixed polymerization method (a method using heat and light), a thermal polymerization initiator and a photopolymerization initiator can be used simultaneously. However, even if carried out by photopolymerization, a certain amount of heat will be generated due to ultraviolet irradiation, and some heat will be generated as the polymerization reaction and the exothermic reaction proceed. Therefore, the composition can additionally include a thermal polymerization initiator.
[0079] Here, any compound that can form radicals by light such as ultraviolet rays may be used as the photopolymerization initiator without limitation.
[0080] For example, the photopolymerization initiator can be one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone. In addition, specific examples of acyl phosphine include diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, ethyl (2,4,6-trimethylbenzoyl) phenyl phosphinate, etc. More various photopolymerization initiators are well disclosed in "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" written by Reinhold Schwalm, page 115, and the present disclosure is not limited thereto.
[0081] In addition, as a thermal polymerization initiator, one or more initiators selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide and ascorbic acid can be used. Specifically, sodium persulfate (Na 2 S 2 O 8 ), potassium persulfate (Na 2 S 2 O8 ), ammonium persulfate ((NH 4 ) 2 S 2 O 8 ) etc. are used as examples of persulfate initiators; and 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoyl)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2)-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid) etc. can be used as examples of azo initiators. More various thermal polymerization initiators are well disclosed in "Principle of Polymerization (Wiley, 1981)" written by Odian, page 203, and the present disclosure is not limited thereto.
[0082] The amount of the polymerization initiator used may be 2 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. When the concentration of the polymerization initiator is too low, the polymerization rate slows down, and a large amount of residual monomers may be extracted from the final product. On the contrary, when the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network shorten, so that the extractable content increases, the pressure absorption decreases, and the physical properties of the polymer are reduced.
[0083] If necessary, the monomer mixture may further include additives such as a thickener, a plasticizer, a storage stabilizer, an antioxidant, and the like.
[0084] In addition, the monomer composition containing the monomer may be, for example, a solution dissolved in a solvent such as water. The solid content of the monomer composition in a solution state, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, may be appropriately adjusted in consideration of the polymerization time and the reaction conditions. For example, the solid content of the monomer composition may be 10 to 80% by weight, 15 to 60% by weight, or 30 to 50% by weight.
[0085] When the monomer composition has a solid content within the above range, the pulverization efficiency during pulverization of the polymer described later can be advantageously controlled while eliminating the need to remove unreacted monomers after polymerization by using the gel effect phenomenon occurring in the polymerization reaction of a high concentration aqueous solution.
[0086] At this time, any solvent capable of dissolving the above components can be used without limitation. For example, the solvent can be selected from at least one of water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butylene glycol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate and N,N-dimethylacetamide.
[0087] In addition, the encapsulated foaming agent refers to a heat-expandable microcapsule foaming agent having a core-shell structure having a core containing hydrocarbons and a shell formed of a thermoplastic resin on the core. Specifically, the hydrocarbon constituting the core is a liquid hydrocarbon with a low boiling point and is easily vaporized by heat. Therefore, when the encapsulated foaming agent is heated, the thermoplastic resin constituting the shell softens, and the liquid hydrocarbon of the core vaporizes. In addition, as the pressure in the capsule increases, the encapsulated foaming agent expands, thereby forming bubbles whose size is increased compared to the existing size.
[0088] Therefore, the encapsulated foaming agent generates hydrocarbon gas, unlike the organic foaming agent that generates nitrogen gas through an exothermic decomposition reaction between monomers involved in polymer production and the inorganic foaming agent that foams carbon dioxide gas by absorbing heat generated in polymer production.
[0089] Depending on the components that make up the core and shell, as well as the weight and diameter of each component, the encapsulated foaming agent can have different expansion characteristics. Therefore, the porosity of the superabsorbent polymer can be controlled by adjusting the encapsulated foaming agent to expand to a desired size.
[0090] Specifically, the encapsulated foaming agent has an average particle size (D 0 ) is in the shape of particles of 5 to 30 μm. It is difficult to manufacture an encapsulated foaming agent having an average diameter of less than 5 μm. When the average diameter of the encapsulated foaming agent exceeds 30 μm, it may be difficult to effectively increase the surface area due to the excessive size of the pores. Therefore, when the encapsulated foaming agent has the above average particle size, it can be determined that the encapsulated foaming agent is suitable for achieving an appropriate pore structure in the resin.
[0091] For example, the average diameter of the encapsulated foaming agent before expansion may be 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 10 μm or more, and 30 μm or less, 25 μm or less, 20 μm or less, 17 μm or less, 16 μm or less, or 15 μm or less.
[0092] The average particle size of the encapsulated foaming agent before expansion (D 0 ) can be determined by measuring the diameter of the encapsulated foaming agent particles as the average Feret particle size using an optical microscope and finding the average value.
[0093] In this case, the capsule thickness of the encapsulated foaming agent may be 2 to 15 μm.
[0094] In addition, the maximum expansion size of the encapsulated foaming agent in air is 20 to 190 μm. Here, "the maximum expansion size of the encapsulated foaming agent" refers to the diameter range of the top 10% by weight of the highly expanded particles after heating the encapsulated foaming agent. It is difficult to produce an encapsulated foaming agent with a maximum expansion size in air of less than 20 μm, and when the maximum expansion size in air exceeds 190 μm, it may be difficult to effectively increase the surface area due to the excessive size of the pores.
[0095] For example, the maximum expanded size of the encapsulated foaming agent in air may be 50 to 190 μm, 70 to 190 μm, 75 to 190 μm, or 80 to 150 μm.
[0096] The maximum expanded size of the encapsulated foaming agent in air can be determined by applying 0.2 g of the encapsulated foaming agent to a glass petri dish, placing it on a hot plate preheated to 150° C. for 10 minutes, and then observing the expanded encapsulated foaming agent with an optical microscope. Then, the average Feret diameter can be obtained by measuring the diameter of the top 10% by weight of the highly expanded particles with an optical microscope.
[0097] In addition, the maximum expansion rate of the encapsulated foaming agent in air is 5 to 15 times. Here, "the maximum expansion rate of the encapsulated foaming agent" refers to the average diameter (D M ) and the average diameter of the encapsulated foaming agent measured before heating (D 0 ) ratio (D M / D 0 ). When the maximum expansion rate of the encapsulated foaming agent in air is less than 5 times, a suitable pore structure cannot be formed in the superabsorbent polymer, and thus there is a problem that a superabsorbent polymer with improved absorption capacity and absorption rate cannot be manufactured. Considering the average diameter of the encapsulated foaming agent before expansion, it is difficult to manufacture an encapsulated foaming agent with a maximum expansion rate in air exceeding 15 times. Therefore, it can be determined that the encapsulated foaming agent with a maximum expansion rate within the above range is suitable for forming a pore structure suitable for superabsorbent polymer.
[0098] For example, the maximum expansion ratio of the encapsulated foaming agent in air may be 5 times or more, 7 times or more, or 8 times or more, and 15 times or less, 13 times or less, 11 times or less, or 10 times or less.
[0099] At this time, the average diameter (D 0 In addition, the average diameter (D M) can be determined by applying 0.2 g of the encapsulated foaming agent to a glass petri dish and placing it on a hot plate preheated to 150° C. for 10 minutes, and then observing the expanded encapsulated foaming agent with an optical microscope. Then, it can be obtained by measuring the diameter of each particle of the first 10% by weight as the average Feret diameter with an optical microscope and then obtaining the average value thereof.
[0100] The expansion characteristics of the encapsulated foaming agent can be further explained in the examples described below.
[0101] The reason for measuring the maximum expansion size and the maximum expansion rate of the encapsulated foaming agent in the air is to determine whether pores having a desired size are formed in the superabsorbent polymer prepared using the encapsulated foaming agent. Specifically, the shape of the foaming agent foaming may vary depending on the preparation conditions of the superabsorbent polymer, so it is difficult to determine the foaming shape. Therefore, the expansion size and the expansion rate are first determined by foaming the encapsulated foaming agent in the air and confirming whether the encapsulated foaming agent is suitable for forming the desired pores.
[0102] Furthermore, the hydrocarbon constituting the core of the encapsulated foaming agent may be at least one selected from the group consisting of n-propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane, n-hexane, isohexane, cyclohexane, n-heptane, isoheptane, cycloheptane, n-octane, isooctane and cyclooctane. Among them, C3 to C5 hydrocarbons (n-propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane) are suitable for forming pores having the above-mentioned size, and isobutane may be the most suitable.
[0103] In addition, the thermoplastic resin constituting the shell of the encapsulated foaming agent may be a polymer formed from at least one monomer selected from the group consisting of (meth)acrylate compounds, (meth)acrylonitrile compounds, aromatic vinyl compounds, vinyl acetate compounds, and halogenated vinyl compounds. Among them, a copolymer of (meth)acrylate and (meth)acrylonitrile may be most suitable for forming pores having the above-mentioned size.
[0104] In addition, the foaming start temperature (T 开始 ) can be 60°C to 120°C, 65°C to 120°C or 70°C to 80°C, and the maximum foaming temperature (T max ) can be 100° C. to 160° C., 105° C. to 155° C., or 110° C. to 120° C. Within the above range, foaming easily occurs during the subsequent thermal polymerization process or drying process, thereby introducing a pore structure into the polymer. The foaming start temperature and the foaming maximum temperature can be measured using a thermomechanical analyzer.
[0105] In addition, relative to 100 parts by weight of water-soluble ethylenically unsaturated monomers, the usage amount of the encapsulated foaming agent can be 0.005 to 1 part by weight. When the content of the foaming agent is less than 0.005 parts by weight, the effect of adding the foaming agent may not be significant. When the content of the foaming agent exceeds 1 part by weight, there are too many pores in the cross-linked polymer, which reduces the gel strength of the prepared superabsorbent polymer and reduces the density, which may cause distribution and storage problems. For example, based on 100 parts by weight of water-soluble ethylenically unsaturated monomers, the usage amount of the encapsulated foaming agent can be more than 0.01 parts by weight, more than 0.03 parts by weight, or more than 0.05 parts by weight, and less than 0.8 parts by weight, less than 0.6 parts by weight, or less than 0.5 parts by weight.
[0106] In addition, a surfactant commonly used as a foam stabilizer may also be added together with the encapsulated foaming agent. For example, the foam stabilizer may include at least one compound selected from the group consisting of an alkyl sulfate compound and a polyoxyethylene alkyl ether compound. Examples of alkyl sulfate compounds include sodium lauryl sulfate, ammonium lauryl sulfate, sodium lauryl ether sulfate, sodium myristyl alcohol polyether sulfate, etc. Examples of polyoxyethylene alkyl ether compounds include polyoxyethylene lauryl ether. Here, the alkyl sulfate compound is an anionic surfactant, and the polyoxyethylene alkyl ether compound is a nonionic surfactant.
[0107] Here, the encapsulated foaming agent and the foam stabilizer may be used in a weight ratio of 1:0.01 to 1:0.5.
[0108] Meanwhile, cross-linking polymerization of the water-soluble ethylenically unsaturated monomer having an acidic group that is at least partially neutralized may be performed without any particular limitation as long as the hydrogel polymer can be formed by thermal polymerization, photopolymerization, or hybrid polymerization.
[0109] Specifically, according to the energy source of polymerization, the polymerization method is mainly divided into thermal polymerization and photopolymerization. In the case of thermal polymerization, it is usually carried out in a reactor equipped with a stirring shaft, such as a kneader. In the case of photopolymerization, it is usually carried out in a reactor equipped with a movable conveyor belt, or in a flat-bottomed container. However, the above-mentioned polymerization method is only an example, and the present invention is not limited thereto.
[0110] For example, the hydrogel polymer can be obtained by supplying hot air to the reactor using a stirring shaft such as a kneader or heating the reactor to perform thermal polymerization. Depending on the shape of the stirring shaft equipped in the reactor, the hydrogel polymer thus obtained can have a size of several centimeters to several millimeters. Specifically, the size of the obtained hydrogel polymer can be changed according to the concentration and injection speed of the monomer composition injected therein, and a hydrogel polymer with a weight average particle size of 2 to 50 mm can be obtained.
[0111] In addition, as mentioned above, when photopolymerization is carried out in a reactor equipped with a movable conveyor or in a container with a flat bottom, the hydrogel polymer obtained can generally be a sheet-like hydrogel polymer with a band width. In this case, the thickness of the polymer sheet can vary according to the concentration, injection speed or injection amount of the monomer composition to be injected, but generally, it is preferred to supply the monomer composition so that a sheet-like polymer with a thickness of about 0.5 to about 5 cm can be obtained. When the thickness of the sheet-like polymer becomes too thin when the monomer mixture is supplied, the production efficiency is low, which is undesirable. When the thickness of the sheet-like polymer is greater than 5 cm, due to the excessive thickness, the polymerization reaction cannot be carried out uniformly over the entire thickness.
[0112] At this time, the water content of the hydrogel polymer thus obtained may be 30 to 70% by weight. For example, the water content of the hydrogel polymer may be 35% by weight or more, 40% by weight or more, or 45% by weight or more, and 70% by weight or less, 65% by weight or less, or 60% by weight or less. When the water content of the hydrogel polymer is too low, it is difficult to ensure an appropriate surface area in the subsequent pulverization step, and thus the pulverization may be ineffective. When the water content of the hydrogel polymer is too high, the pressure in the subsequent pulverization step increases, and thus the pulverization may be difficult to be performed to a desired particle size.
[0113] Meanwhile, the "water content" in this specification refers to the content of water in the total weight of the hydrogel polymer, which refers to a value obtained by subtracting the weight of the polymer after drying from the weight of the hydrogel polymer. Specifically, the water content is defined as a value calculated as a weight loss due to evaporation of water from the polymer in the process of increasing the temperature of the granular polymer for drying by infrared heating. At this time, the drying conditions for measuring the water content are as follows: the temperature is increased to about 180°C and maintained at 180°C, and the total drying time is 40 minutes, including a 5-minute heating step.
[0114] The hydrogel polymer formed by step 1 has a three-dimensional network structure in which a main chain formed by polymerization of a water-soluble ethylenically unsaturated monomer is cross-linked by an internal cross-linking agent. When the hydrogel polymer has a three-dimensional network structure, water retention capacity and pressure absorbency, which are general physical properties of superabsorbent polymers, can be significantly improved compared to a case of having a two-dimensional linear structure that is not further cross-linked by an internal cross-linking agent.
[0115] (Step 2)
[0116] The above step is a step of preparing a coarsely pulverized hydrogel polymer, wherein hydrophobicity is imparted to the surface of the hydrogel polymer by mixing a carboxylic acid additive with the hydrogel polymer before coarse pulverization.
[0117] At this time, the carboxylic acid additive is at least one selected from the group consisting of carboxylic acids represented by Chemical Formula 1 and metal salts thereof. Specifically, the carboxylic acid additive is at least one selected from the group consisting of carboxylic acids represented by Chemical Formula 1, alkali metal salts of carboxylic acids represented by Chemical Formula 1, and alkaline earth metal salts of carboxylic acids represented by Chemical Formula 1. More specifically, the carboxylic acid additive is one of carboxylic acids represented by Chemical Formula 1, alkali metal salts of carboxylic acids represented by Chemical Formula 1, and alkaline earth metal salts of carboxylic acids represented by Chemical Formula 1.
[0118] In Chemical Formula 1, A is a hydrophobic part and may be a C5 to C21 straight or branched alkyl group. However, the case where A is a straight chain alkyl group is more advantageous in suppressing the aggregation of crushed particles and improving dispersibility. When A is an alkyl group having less than 5 carbon atoms, there is a problem that the chain is short and thus the aggregation of crushed particles cannot be effectively controlled. When A is an alkyl group having more than 21 carbon atoms, the fluidity of the additive may be reduced, and thus the carboxylic acid additive may not be effectively mixed with the hydrogel polymer, and the cost of the composition may increase due to the increase in the cost of the additive.
[0119] Specifically, in Chemical Formula 1, A may be a C5 to C21 straight chain alkyl group, such as n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-icosanyl, or n-heneicosanyl.
[0120] More specifically, A may be a C6 to C18 straight chain alkyl group. For example, A may be -C 6 H 13 , -C 11 H 23 , -C 12 H 25 , -C 17 H 35 or -C 18 H 37 .
[0121] In addition, (B 1 -B 2 ) portion improves the adsorption performance on the polymer surface, which is insufficient in the case of only C portion. 2 When the number of carbon atoms is 3 or more, B 1 The distance between the A portion and the C portion increases, and the adsorption performance to the hydrogel polymer may deteriorate.
[0122] Here, R 1 and R 2can each independently be a C1 to C4 straight chain or branched alkyl group. More specifically, R 1 and R 2 Each of the groups R and R can be independently methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl or tert-butyl. Since the additive can be adsorbed on the superabsorbent polymer particles, it is advantageous that the molecular structure of the additive is not large, so R 1 and R 2 Both can be methyl.
[0123] In addition, n of Chemical Formula 1 may be 1, 2 or 3. More specifically, considering (B 1 -B 2 ) part is used to enhance the adsorption performance relative to part C and how long the molecular length is required to effectively adsorb the carboxylic acid additive on the hydrogel polymer, indicating that (B 1 -B 2 ) is preferably 1.
[0124] Specifically, in Chemical Formula 1, B 1 Can be where * is the bonding site to the neighboring atom.
[0125] For example, B 1 Can be
[0126] In addition, in Chemical Formula 1, B 2 Can be where * is the bonding site to the neighboring atom.
[0127] At this time, in order to improve the adsorption performance of the additive to the cross-linked polymer together with part C, B 2 Preferably
[0128] In addition, in Chemical Formula 1, the C portion is a carboxyl group (COOH) as a hydrophilic portion, and when the carboxylic acid additive is a salt, it is a carboxylate group (COO - ).
[0129] In other words, the carboxylic acid additive may be a compound represented by the following Chemical Formula 1a:
[0130] [Chemical formula 1a]
[0131]
[0132] In Chemical Formula 1a,
[0133] M is for H + , monovalent cations of alkali metals or divalent cations of alkaline earth metals,
[0134] If M is H + or a monovalent cation of an alkali metal, k is 1, and if it is a divalent cation of an alkaline earth metal, k is 2, and
[0135] A. B 1 , B 2 and n are as defined in Chemical Formula 1.
[0136] More specifically, when the carboxylic acid-based additive is an alkali metal salt of a carboxylic acid represented by Chemical Formula 1, the additive may be represented by the following Chemical Formula 1':
[0137] [Chemical Formula 1']
[0138]
[0139] In Chemical Formula 1',
[0140] M 1 is an alkali metal, such as sodium or potassium, and
[0141] A. B 1 , B 2 and n are as defined in Chemical Formula 1.
[0142] In addition, when the carboxylic acid additive is an alkaline earth metal salt of a carboxylic acid represented by Chemical Formula 1, the additive may be represented by the following Chemical Formula 1":
[0143]
Chemical formula 1"
[0144]
[0145] In the chemical formula 1", M 2 is an alkaline earth metal, such as calcium, and
[0146] A. B 1 , B 2 and n are as defined in Chemical Formula 1.
[0147] For example, the carboxylic acid additive may be any carboxylic acid selected from the group consisting of:
[0148]
[0149]
[0150] Alternatively, the carboxylic acid additive may be any alkali metal salt selected from the group consisting of:
[0151]
[0152]
[0153] In the above formula,
[0154] M 1 Each is independently an alkali metal.
[0155] Alternatively, the carboxylic acid additive may be any alkaline earth metal salt selected from the group consisting of:
[0156]
[0157]
[0158] In the above formula,
[0159] M 2 Each is independently an alkaline earth metal.
[0160] For example, the carboxylic acid additive may be any one of the compounds represented by the following Chemical Formulas 1-1 to 1-7, but is not limited thereto:
[0161]
[0162] At the same time, based on 100 parts by weight of the hydrogel polymer, the amount of the carboxylic acid additive used can be 0.01 to 1.0 parts by weight. When the additive is used too little, it cannot be uniformly adsorbed on the surface of the hydrogel polymer, which may cause the particles to re-aggregate after crushing. When too much additive is used, the overall physical properties of the superabsorbent polymer finally prepared may deteriorate. For example, based on 100 parts by weight of the hydrogel polymer, the amount of the carboxylic acid additive used can be 0.01 parts by weight or more, 0.015 parts by weight or more, or 0.1 parts by weight or more, and less than 1.0 parts by weight, less than 0.8 parts by weight, less than 0.6 parts by weight, or less than 0.5 parts by weight.
[0163] The method of mixing the additive with the hydrogel polymer is not particularly limited as long as it is a method that can uniformly mix it with the hydrogel polymer, and can be appropriately selected and used. Specifically, the additive can be dry-mixed, dissolved in a solvent and then mixed, or melted and then mixed.
[0164] For example, the additive may be mixed in the form of a solution dissolved in a solvent. At this time, any type of inorganic solvent or organic solvent may be used without limitation, but water is most preferred as the solvent in consideration of the ease of drying and the cost of the solvent recovery system. In addition, a method of mixing the additive in the form of a solution and the hydrogel polymer in a reaction tank, a method of spraying the solution after the hydrogel polymer is placed in a mixer, and a method of continuously supplying the hydrogel polymer and the solution to a continuously operating mixer for mixing may be used.
[0165] By mixing the hydrogel polymer with the additive and then coarsely pulverizing the mixture, a coarsely pulverized product of the hydrogel polymer mixed with the additive can be prepared.
[0166] At this time, the pulverizer used is not particularly limited, and can be selected from any one of the group consisting of a vertical pulverizer, a turbine cutter, a turbine grinder, a rotary cutting pulverizer, a cutter mill, a disc mill, a chip crusher, a crusher, a shredder, and a disc cutter. However, the present disclosure is not limited thereto.
[0167] Among them, the coarse pulverization can be performed by a shredder, more specifically, by a meat slicer. At this time, the meat slicer may include a pulverizing module having one or more perforated plates, and each perforated plate may be provided with a plurality of finely cut holes of a certain size, through which the hydrogel polymer may pass. In addition, the aperture of the finely cut holes of the porous plate may be 3 mm to 16 mm. In other words, it can be seen that the hydrogel polymer mixed with the additive is pulverized by pushing it so that the hydrogel polymer is pulverized while passing through the finely cut holes of the porous plate. At this time, an extruder may be used to push the hydrogel polymer out. For example, a single screw or multi-screw extruder may be used.
[0168] Therefore, the particle size of the coarsely pulverized hydrogel polymer may be 300 to 5000 μm. It is not technically easy to pulverize the polymer to a particle size less than 300 μm, and when the particle size exceeds 5000 μm, the effect of improving the efficiency of the subsequent drying step is not significant.
[0169] At the same time, at least some of the additives contained in the coarsely pulverized product may be present on the surface of the coarsely pulverized hydrogel polymer. Here, "at least some of the additives are present on the surface of the coarsely pulverized hydrogel polymer" means that at least some of the additives are adsorbed or bound to the surface of the coarsely pulverized hydrogel polymer. Specifically, the additives may be physically or chemically adsorbed on the surface of the coarsely pulverized hydrogel polymer. More specifically, the hydrophilic functional groups of the additives may be physically adsorbed on the hydrophilic part of the surface of the coarsely pulverized hydrogel polymer through intermolecular forces such as dipole-dipole interactions. In this way, the hydrophilic part of the additive is physically adsorbed on the surface of the coarsely pulverized hydrogel polymer, thereby surrounding the surface, while the hydrophobic part of the additive is not adsorbed on the surface of the polymer particles, because the polymer particles can be coated with the additive in the form of a micelle structure. This is because the carboxylic acid additive is not added during the polymerization of the water-soluble ethylenically unsaturated monomer, but is added after the polymer is formed. Therefore, compared with the case where the additive is added during the polymerization process and the additive is present inside the polymer, the re-aggregation of the coarsely pulverized hydrogel polymer can be further suppressed.
[0170] (Step 3)
[0171] The above step is a step of drying the pulverized product to dry the moisture of the water-containing superabsorbent polymer particles. Specifically, the pulverized product can be dried so that the moisture content of each of the plurality of superabsorbent polymer particles included in the prepared superabsorbent polymer is about 10 wt % or less, specifically, about 0.01 to about 10 wt %.
[0172] Here, the drying temperature in the drying step may be about 150 to about 250° C. When the drying temperature is lower than 150° C., the drying time may become too long, and the physical properties of the super absorbent polymer finally formed may be reduced. When the drying temperature exceeds 250° C., only the polymer surface is excessively dried, fine powder may be generated in the subsequent pulverization process, and the physical properties of the super absorbent polymer may be reduced. Therefore, the drying may be preferably performed at a temperature of about 150 to about 200° C., more preferably at a temperature of about 160 to about 180° C.
[0173] Meanwhile, considering processing efficiency, the drying time may be about 20 minutes to about 90 minutes, but is not limited thereto.
[0174] The drying method in the drying step is not particularly limited as long as it is generally used in the drying process of the hydrogel polymer. Specifically, the drying step can be performed by hot air supply, infrared irradiation, microwave irradiation, ultraviolet irradiation, etc. After the drying step, the moisture content of the polymer can be about 5 to about 10% by weight.
[0175] Subsequently, a step of pulverizing the dried polymer obtained by the drying step is performed.
[0176] The base resin as the polymer powder obtained after the pulverization step may have a particle size of about 150 to about 850 μm. As a pulverizer for pulverizing to such a particle size, a pin mill, a hammer mill, a spiral mill, a roller mill, a disc mill, a jog mill, etc. may be used, but the present invention is not limited thereto.
[0177] In order to manage the physical properties of the superabsorbent polymer powder to be commercialized after the pulverization step, the base resin obtained after pulverization is classified according to the particle size. Preferably, the polymer with a particle size of about 150 to about 850 μm is classified, and the surface crosslinking reaction step can be performed only on the base resin with such a particle size. In this case, the particle size can be measured according to EDANA (European Disposables and Nonwovens Association) WSP 220.3.
[0178] (Step 4)
[0179] The above step is a step of further crosslinking the crosslinked polymer contained in the base resin particles using a surface crosslinking agent to form a super absorbent polymer in which a surface crosslinked layer is formed on the surface of the base resin, more specifically, on at least a portion of the surface of each base resin particle.
[0180] In other words, the surface crosslinking step is a step in which the crosslinking density near the surface of the superabsorbent polymer particles is increased relative to the crosslinking density inside the particles. Typically, a surface crosslinking agent is applied to the surface of the superabsorbent polymer particles. Therefore, the reaction occurs on the surface of the superabsorbent polymer particles, which improves the crosslinking properties of the particle surface without significantly affecting the inside of the particles. Therefore, the surface crosslinked superabsorbent polymer particles have a higher degree of crosslinking near the surface than inside.
[0181] As the surface crosslinking agent, any surface crosslinking agent conventionally used for preparing superabsorbent polymers can be used without any particular limitation. Examples of the surface crosslinking agent may include: at least one polyol selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propylene glycol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; at least one carbonate compound selected from the group consisting of ethylene carbonate, propylene carbonate and glycerol carbonate; epoxy compounds such as ethylene glycol diglycidyl ether and glycerol polyglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; mono-, di- or poly-oxazolidinone compounds; cyclic urea compounds, etc.
[0182] Specifically, one or more, or two or more, or three or more of the above-mentioned surface crosslinking agents may be used as the surface crosslinking agent, and the surface crosslinking agent may be the same as the internal crosslinking agent.
[0183] The content of the surface crosslinking agent can be appropriately selected according to the type of the surface crosslinking agent specifically added or the reaction conditions. Based on 100 parts by weight of the base resin, its usage amount can be about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.02 to about 2 parts by weight. When the content of the surface crosslinking agent is too little, the surface crosslinking reaction hardly occurs, and when it exceeds 5 parts by weight based on 100 parts by weight of the base resin, absorbency such as water retention capacity may deteriorate due to excessive surface crosslinking.
[0184] In addition, the method for mixing the surface crosslinking agent with the base resin is not particularly limited. For example, a method of adding the surface crosslinking agent and the base resin powder to a reactor for mixing, a method of spraying the surface crosslinking agent onto the base resin powder, or a method of mixing the base resin and the surface crosslinking agent while continuously supplying them to a continuously operating mixer can be used.
[0185] When adding a surface crosslinking agent, water may be mixed therein to add the surface crosslinking agent in the form of a surface crosslinking solution. When water is added thereto, there is an advantage that the surface crosslinking agent can be uniformly dispersed in the polymer. At this time, in order to induce uniform dispersion of the surface crosslinking agent, prevent agglomeration of the polymer powder, and optimize the surface penetration depth of the surface crosslinking agent, the amount of water to be added may be about 1 to about 10 parts by weight based on 100 parts by weight of the base resin.
[0186] According to one embodiment of the present disclosure, in addition to water, an alcohol solvent such as methanol may also be added. Alcohol solvents such as methanol do not participate in the surface cross-linking reaction and act as solvents. Therefore, the surface cross-linking solution is slowly absorbed into the base resin, thereby achieving a uniform application effect. At this time, based on 100 parts by weight of the base resin, the content of the alcohol solvent may be about 1 part by weight or more, about 2 parts by weight or more, or about 3 parts by weight or more, and about 10 parts by weight or less, about 8 parts by weight or less, or about 6 parts by weight or less.
[0187] The surface cross-linking reaction can be performed by heating the base resin to which the surface cross-linking solution containing the surface cross-linking agent and the solvent is added at about 100 to about 150° C., preferably at about 110 to about 140° C., for about 15 to about 80 minutes, preferably about 20 to about 70 minutes. When the temperature is lower than 100° C., the surface cross-linking reaction may not sufficiently occur. When it exceeds 150° C., propylene glycol or propylene carbonate contained as a solvent may participate in the surface cross-linking reaction, and an additional surface cross-linking reaction may be performed by these compounds.
[0188] The heating method for the surface cross-linking reaction is not particularly limited. A thermal medium can be provided thereto or a heat source can be directly provided thereto. At this time, the available thermal medium can be a heating fluid such as steam, hot air, hot oil, but the present invention is not limited thereto. In addition, the temperature of the thermal medium provided thereto can be appropriately selected by considering the mode of the thermal medium, the heating rate and the target temperature of the heating. Meanwhile, an electric heater or a gas heater can be used as the heat source directly provided, but the present invention is not limited thereto.
[0189] In addition, at least one inorganic material selected from the group consisting of silica, clay, alumina, silica-alumina composite, titanium dioxide, zinc oxide and aluminum sulfate may be added together with the surface crosslinking agent in step 4. The inorganic material may be used in a powder or liquid state, and in particular, aluminum oxide powder, silica powder, silica-alumina powder, titanium dioxide powder, aluminum sulfate powder or nano-silica solution may be used.
[0190] In addition, based on 100 parts by weight of the base resin, the use amount of the inorganic material can be 0.001 to 0.3 parts by weight. When the amount of the inorganic material based on 100 parts by weight of the base resin is greater than 0.3 parts by weight, the surface crosslinking degree of the polymer particles may increase and the pressure absorption may decrease, which is undesirable. However, when a small amount of inorganic material is further added within the above range, there is an advantage that permeability and anti-caking efficiency can be further improved. For example, based on 100 parts by weight of the base resin, the use amount of the inorganic material can be more than 0.01 parts by weight, more than 0.05 parts by weight, more than 0.1 parts by weight, and less than 0.3 parts by weight.
[0191] Furthermore, as described above, after forming a surface crosslinked layer on the surface of the base resin, an inorganic material may be further mixed.
[0192] As the inorganic material, at least one inorganic material selected from the group consisting of silica, clay, alumina, a silica-alumina composite and titania can be used, and silica is preferred.
[0193] The inorganic material may be used in an amount of 0.001 parts by weight or more, or 0.01 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, or 1 part by weight or less, based on 100 parts by weight of the super absorbent polymer.
[0194] In order to manage the physical properties of the superabsorbent polymer to be commercialized, the superabsorbent polymer obtained after the surface crosslinking step may be further classified according to particle size. It is preferred to classify polymers with a particle size of about 150 to 850 μm and use only superabsorbent polymers with this particle size as the final product.
[0195] In addition, the superabsorbent polymer prepared by the above method may further include, in addition to the superabsorbent polymer particles and the carboxylic acid additive, a hydrogel polymer obtained by decomposing B in the drying process after the additive and the hydrogel polymer are pulverized. 1 Compounds formed by ester bonds.
[0196] Specifically, when the additive is wherein n is 1 and B 1When the compound is -OCO-, the superabsorbent polymer may also include an alcohol having an A-OH structure and an alcohol having a HOOC-B structure. 2 -C structure compounds.
[0197] In addition, when the additive is wherein n is 1 and B 1 When the compound is -COO-, the superabsorbent polymer may also include a carboxylic acid having an A-COOH structure and a HO-B 2 -C structure compounds.
[0198] In addition, when the additive is wherein n is 1 and B 1 -COOCH(R 1 )COO-, the superabsorbent polymer may also include a carboxylic acid having an A-COOH structure and a HOCH(R 1 )COO-B 2 -C structure compounds.
[0199] Since the super absorbent polymer also includes a compound formed by decomposing the ester bond in the additive molecule, the fluidity of the additive is increased and the re-aggregation phenomenon after pulverization can be further prevented.
[0200] In addition, in the above-mentioned preparation method, a compound containing a glucose unit having a plurality of hydroxyl groups in the molecule, such as microcrystalline cellulose, may not be used. For example, when the superabsorbent polymer composition contains microcrystalline cellulose having an average particle size of 1 to 10 μm, such as microcrystalline cellulose obtained from FMC and represented by the following chemical formula 3: In the case of PH-101, the aggregation of the finally prepared superabsorbent polymer particles may not be suppressed due to the large number of hydroxyl groups, and thus the effects of the above additives may not be effectively exhibited.
[0201] [Chemical formula 3]
[0202]
[0203] The super absorbent polymer obtained by the above-mentioned preparation method can satisfy the following physical properties by achieving a balance between absorption rate and absorption properties.
[0204] The centrifuge retention capacity (CRC) measured according to EDANA WSP 241.3 may be 25 g / g or more, 26 g / g or more, 27 g / g or more, 28 g / g or more, or 29 g / g or more, and 35 g / g or less, 33 g / g or less, or 31 g / g or less.
[0205] In addition, the superabsorbent polymer may have an absorbency under pressure (AUP) at 0.3 psi of 20 g / g or more, 23 g / g or more, 25 g / g or more, 26 g / g or more, or 28 g / g or more, and 33 g / g or less, 32 g / g or less, or 30 g / g or less, when measured according to EDANA WSP 242.3.
[0206] In addition, the vortex time (absorption rate) of the superabsorbent polymer at 24°C may be 30 seconds or less, 29 seconds or less, 28 seconds or less, 27 seconds or less, 26 seconds or less, or 25 seconds or less. In addition, since the lower the vortex time, the better it is evaluated, the lower limit is theoretically 0 seconds, but it may be 10 seconds or more, 15 seconds or more, 18 seconds or more, or 20 seconds or more. Here, the method for measuring the vortex time is specifically described in the experimental examples described later.
[0207] In addition, the permeability (unit: seconds) of the superabsorbent polymer measured according to the following equation 3 may be 40 seconds or less, 30 seconds or less, 25 seconds or less, 20 seconds or less, 19 seconds or less, or 15 seconds or less. Since the lower the permeability, the better it is evaluated, the lower limit is theoretically 0 seconds, but it may also be 5 seconds or more, 7 seconds or more, 10 seconds or more, or 13 seconds or more:
[0208] [Equation 3]
[0209] Permeability (seconds) = T1-B
[0210] In equation 3,
[0211] T1 is the time required for the liquid level to drop from 40 mL to 20 mL after adding 0.2±0.0005 g of graded (30#~50#) superabsorbent polymer sample to the chromatographic tube, adding saline to make the volume 50 mL, and standing for 30 minutes.
[0212] B is the time required for the liquid level in a chromatographic tube filled with saline to drop from 40 mL to 20 mL.
[0213] In addition, the anti-caking (A / C) efficiency of the superabsorbent polymer calculated by the following equation 4 may be 50% or more, 55% or more, 56% or more, 58% or more, 60% or more, or 67% or more. Since the higher the anti-caking efficiency is evaluated to be better, the upper limit is theoretically 100%, but may also be 99% or less, 98% or less, or 80% or less:
[0214] [Equation 4]
[0215]
[0216] In equation 4,
[0217] W 5is the weight (g) of a petri dish with a diameter of 90 mm and a height of 15 mm,
[0218] S 1 The weight is W 5 2±0.01 g of the superabsorbent polymer sample is uniformly applied to a culture dish, the culture dish with the sample applied is placed in a constant temperature and humidity chamber set at 40°C and 80% RH for 10 minutes, it is taken out, turned over on an A4 paper, and then left for 5 minutes, and the weight (g) of the superabsorbent polymer sample that falls on the A4 paper is measured, and
[0219] S 2 is the measurement S 1 The weight of the culture dish at .
[0220] Hereinafter, the present invention will be described in more detail with reference to Examples. However, these Examples are for illustrative purposes only, and the present invention is not limited to these Examples.
[0221] <Example>
[0222] Preparation of encapsulated foaming agent
[0223] As the encapsulated foaming agent used in the examples, F-36D manufactured by Matsumoto was prepared, which had a core of isobutane and a shell of a copolymer of acrylate and acrylonitrile. At this time, the foaming start temperature (T 开始 ) is 70℃ to 80℃, the maximum foaming temperature (T max ) is 110℃ to 120℃.
[0224] The diameter of each encapsulated foaming agent was measured as an average Feret diameter using an optical microscope. Then, the average value of the diameters of the encapsulated foaming agents was obtained and defined as the average diameter of the encapsulated foaming agent.
[0225] In addition, in order to confirm the expansion characteristics of the encapsulated foaming agent, 0.2 g of the encapsulated foaming agent prepared above was applied to a glass petri dish and then placed on a hot plate preheated to 150° C. for 10 minutes. The encapsulated foaming agent expands slowly when heated, and an optical microscope was used to observe to determine the maximum expansion rate and maximum expansion size of the encapsulated foaming agent in air.
[0226] The diameter of the first 10 wt% of the highly expanded particles after heating the encapsulated foaming agent is defined as the maximum expansion size, and the average diameter (D M ) and the average diameter (D 0 ) ratio (D M / D 0 ) is defined as the maximum expansion rate.
[0227] The average diameter of the prepared encapsulated foaming agent before expansion is 13 μm, the maximum expansion multiple in the air is about 9 times, and the maximum expansion size is about 80 to 150 μm.
[0228] Example 1
[0229] (Step 1)
[0230] 100 g (1.388 mol) of acrylic acid, 0.001 g of polyethylene glycol diacrylate (Mn=508) and 0.24 g of ethylene glycol diglycidyl ether as internal crosslinking agents, 0.008 g of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as a photopolymerization initiator, 0.125 g of sodium persulfate as a thermal polymerization initiator, 123.5 g of a 32% caustic soda solution, 0.1 g of an encapsulated foaming agent (F-36D) and 0.02 g of an aqueous solution of sodium dodecyl sulfate (SDS) were mixed with 66.0 g of water in a 3 L glass container equipped with a stirrer and a thermometer at room temperature to prepare a monomer composition having a total solid content of 42.0 wt % (neutralization degree of acrylic acid: 70 mol %).
[0231] Thereafter, the monomer composition was supplied at 500 to 2000 mL / min onto a conveyor belt having a width of 10 cm and a length of 2 m, which was rotated at a speed of 50 cm / min. Also, while the monomer composition was supplied, the irradiation intensity was 10 mW / cm 2 The reaction mixture was irradiated with ultraviolet light for 60 seconds to carry out a polymerization reaction, thereby obtaining a hydrogel polymer in the form of a sheet having a moisture content of 50% by weight.
[0232] (Step 2)
[0233] Subsequently, sodium stearoyl-2-lactate (Almax-6900, manufactured by IlshinWells) represented by the following chemical formula 1-6 was mixed with a hydrogel polymer obtained by a polymerization reaction, which was performed by applying sodium stearoyl-2-lactate in the form of an aqueous solution in high-temperature water to the hydrogel polymer in a sheet form, thereby applying 0.4 parts by weight based on 100 parts by weight of the hydrogel polymer. Then, it was coarsely pulverized using a meat cutter so that the particle size of the hydrogel polymer was 300 μm to 5000 μm. As a meat cutter, a meat cutter having a porous plate provided with a plurality of fine cutting holes having a pore size of 3 mm was used. And, the moisture content of the coarsely pulverized hydrogel polymer particles was 46% by weight.
[0234] [Chemical formula 1-6]
[0235]
[0236] (Step 3)
[0237] Thereafter, the pulverized product was dried by flowing hot air at 180° C. for 43 minutes using a convection oven capable of changing wind direction up and down, thereby obtaining a base resin in a powder form.
[0238] (Step 4)
[0239] Subsequently, a surface crosslinking solution was prepared with 5.8 g of ultrapure water, 5.0 g of methanol, 0.02 g of ethylene glycol diglycidyl ether (EJ-1030S) and 0.01 g of glycerol polyglycidyl ether (EJ-300), which was added to 100 g of the obtained base resin, followed by mixing for 1 minute, and then a surface crosslinking reaction was performed at 140° C. for 35 minutes. Then, the obtained product was classified with an ASTM standard sieve to obtain a superabsorbent polymer powder having a particle size of 150 to 850 μm. Thereafter, 0.013 g of fumed silica ( 200) to prepare the final superabsorbent polymer.
[0240] Example 2
[0241] A super absorbent polymer was prepared in the same manner as in Example 1, except that 0.1 g of aluminum sulfate (AlS) was added to the surface cross-linking solution of Example 1.
[0242] Example 3
[0243] A super absorbent polymer was prepared in the same manner as in Example 1, except that 0.2 g of aluminum sulfate was added to the surface cross-linking solution of Example 1.
[0244] Example 4
[0245] A super absorbent polymer was prepared in the same manner as in Example 1, except that 0.3 g of aluminum sulfate was added to the surface cross-linking solution of Example 1.
[0246] Example 5
[0247] A super absorbent polymer was prepared in the same manner as in Example 1, except that monohexyl maleate represented by the following Chemical Formula 1-2 was used instead of sodium stearoyl-2-lactylate in step 2 of Example 1. Here, monohexyl maleate represented by the following Chemical Formula 1-2 was prepared by mixing maleic anhydride and 1-hexanol at a molar ratio of 1:1 and then reacting at 60°C for 3 hours.
[0248] [Chemical formula 1-2]
[0249]
[0250] Example 6
[0251] A super absorbent polymer was prepared in the same manner as in Example 1, except that monolauryl maleate represented by the following Chemical Formula 1-1 was used instead of sodium stearoyl-2-lactylate in step 2 of Example 1. Here, monolauryl maleate represented by the following Chemical Formula 1-1 was prepared by mixing maleic anhydride and 1-dodecanol at a molar ratio of 1:1 and then reacting at 60°C for 3 hours.
[0252] [Chemical formula 1-1]
[0253]
[0254] Example 7
[0255] A super absorbent polymer was prepared in the same manner as in Example 1, except that sodium lauroyl-2-lactylate (manufactured by Ilshin Wells) represented by the following Chemical Formula 1-7 was used instead of sodium stearoyl-2-lactylate in step 2 of Example 1.
[0256] [Chemical formula 1-7]
[0257]
[0258] Comparative Example 1
[0259] A super absorbent polymer was prepared in the same manner as in Example 1, except that in step 2 of Example 1, sodium stearoyl-2-lactylate was not used.
[0260] Comparative Example 2
[0261] A super absorbent polymer was prepared in the same manner as in Example 1, except that sodium stearoyl-2-lactylate was not used in step 2 of Example 1, and 0.3 g of aluminum sulfate was added to the surface cross-linking solution of Example 1.
[0262] Comparative Example 3
[0263] A super absorbent polymer was prepared in the same manner as in Example 1, except that sodium stearoyl-2-lactylate was not used in step 2 of Example 1, and 0.1 g of aluminum sulfate was added to the surface cross-linking solution of Example 1.
[0264] Experimental Example 1
[0265] The centrifuge retention capacity (CRC), pressure absorption (AUP), eddy flow time, permeability and anti-caking efficiency of the superabsorbent polymers prepared in the examples and comparative examples were evaluated in the following manner, and the results are shown in the following Table 1. Unless otherwise specified, all procedures were carried out in a constant temperature and humidity chamber (23 ± 2°C, relative humidity 45 ± 10%). In order to prevent measurement errors, the average value of three measurements was taken as the measurement data. In addition, the physiological saline or saline used to evaluate the following physical properties refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution.
[0266] (1) Centrifugal retention capacity (CRC)
[0267] The centrifuge retention capacity of the absorbency under unloaded conditions of each polymer composition was measured according to the EDANA (European Disposables and Nonwovens Association) WSP 241.3 method.
[0268] Specifically, each polymer composition prepared in the examples and comparative examples was graded through a #30-50 sieve to obtain a polymer composition. 0 The polymer composition (g, about 0.2g) was uniformly inserted into a non-woven bag and sealed, and then immersed in saline (0.9 wt%) at room temperature. After 30 minutes, the bag was centrifuged at 250G for 3 minutes to dehydrate, and the weight of the bag was measured. 2 (g). In addition, after the same operation without using the resin, the weight W of the sealed bag was measured. 1 (g).
[0269] Then, CRC (g / g) was calculated according to the following Equation 1 by using the obtained weight value.
[0270] [Equation 1]
[0271] CRC(g / g)={[W 2 (g)-W 1 (g)] / W 0 (g)}–1
[0272] (2) Absorbency under applied pressure (AUP)
[0273] The superabsorbent polymers prepared in Examples and Comparative Examples were measured for their pressure absorbency at 0.3 psi according to the EDANA WSP 242.3 method.
[0274] First, in the measurement of absorbency under pressure, the fractionated polymers measured by the above-mentioned CRC were used.
[0275] Specifically, a 400-mesh stainless steel screen was installed in the bottom of a plastic cylinder with an inner diameter of 25 mm. At room temperature and 50% humidity, W 0(g, 0.16g) of superabsorbent polymer composition is evenly dispersed on the screen. Thereafter, a piston that can evenly provide a 0.3psi load is placed on the composition. Here, the outer diameter of the piston is slightly less than 25mm, there is no gap with the inner wall of the cylinder, and the up and down movement (jig-jog) of the cylinder is not interrupted. At this time, the weight W of the measuring device is 3 (g).
[0276] Subsequently, a glass filter having a diameter of 90 mm and a thickness of 5 mm was placed in a culture dish having a diameter of 150 mm, and saline (0.9 wt % sodium chloride) was poured into the culture dish. At this time, the saline was poured until the surface level of the saline was equal to the upper surface of the glass filter. A piece of filter paper having a diameter of 90 mm was placed thereon. After placing the measuring device on the filter paper, the liquid was absorbed under load for 1 hour. After 1 hour, the measuring device was lifted and the weight W was measured. 4 (g).
[0277] Then, the pressurization absorbency (g / g) was calculated according to the following Equation 2 by using the obtained weight value.
[0278] [Equation 2]
[0279] AUP(g / g)=[W 4 (g)-W 3 (g)] / W 0 (g)
[0280] (3) Eddy current time
[0281] The vortex time of the super absorbent polymers prepared in Examples and Comparative Examples was measured in the following manner.
[0282] ① First, after installing a thermometer in a 100 mL flat-bottom beaker, add 50 g of 0.9% physiological saline and place a magnetic bar (8 mm in diameter, 30.0 mm in length) therein.
[0283] ② Next, while stirring the magnetic bar at 600 rpm, after confirming that the temperature is maintained at 24°C and a vortex is generated by stirring, remove the thermometer.
[0284] ③ Then, add 2 g of the super absorbent polymer sample, measure the time from the addition of the sample to the disappearance of the vortex and the flattening of the liquid surface in seconds, and use it as the vortex time.
[0285] (4) Permeability
[0286] The permeability of the super absorbent polymers prepared in Examples and Comparative Examples was measured in the following manner.
[0287] Specifically, the lines were marked on the liquid level of 20 mL and 40 mL of the chromatographic tube (F20 mm) into which the piston was inserted. As the chromatographic tube used at this time, a tube with a length of 250 mm and a diameter of 22 mm was used, which was equipped with a glass filter (Glass Fritted Filter Disc, P3: 16-40 μm) with a diameter of 20 mm and a lower valve (cock). As the piston, a piston weighing 65 g was used to apply a pressure of 0.3 psi per unit area.
[0288] After that, remove the piston and add water in reverse so that no bubbles are generated between the glass filter and the lower valve at the bottom of the chromatographic tube until about 10 ml of the tube is filled. Then, wash 2 to 3 times with 0.9 wt % saline and fill with more than 40 ml of saline. After that, introduce the piston into the chromatographic tube, open the lower valve, and then record the time (B) for the liquid level to drop from the 40 ml line to the 20 ml line.
[0289] Then, 10 mL of saline solution was left in the chromatographic tube, 0.2 ± 0.0005 g of a graded (30# to 50#) superabsorbent polymer sample was added, and saline solution was added to make the volume of the saline solution 50 mL, and then the solution was allowed to stand for 30 minutes. After that, the piston was introduced into the chromatographic tube, and the solution was allowed to stand for 1 minute. The valve at the bottom of the chromatographic tube was opened, and the time (T1) for the liquid level to drop from the 40 mL line to the 20 mL line was recorded. Then, the time (unit: seconds) of T1-B was calculated according to the following equation 3.
[0290] [Equation 3]
[0291] Permeability (seconds) = T1-B
[0292] In equation 3,
[0293] T1 is the time taken for the liquid level to drop from 40 mL to 20 mL after adding 0.2±0.0005 g of graded (30#~50#) superabsorbent polymer sample to the chromatographic tube, adding saline to make the volume of saline 50 mL, and standing for 30 minutes.
[0294] B is the time taken for the liquid level to drop from 40 mL to 20 mL in a chromatographic tube filled with saline.
[0295] (5) Anti-caking (A / C) efficiency
[0296] The anti-blocking efficiency of the super absorbent polymers prepared in Examples and Comparative Examples was measured in the following manner. At this time, an apparatus for measuring the anti-blocking efficiency was prepared as follows.
[0297] -Electronic balance (accuracy: 0.01g)
[0298] - Constant temperature and humidity chamber (temperature: 40°C, humidity: 80% RH)
[0299] -Petri dishes ( 90mm, height: 15mm)
[0300] - Stopwatch
[0301] -A4 paper
[0302] ① First, measure the weight of the prepared culture dish (W 5 ).
[0303] ② Next, apply 2±0.01 g of the super absorbent polymer sample evenly on the weighed petri dish.
[0304] ③ Then, place the culture dish containing the superabsorbent polymer sample in a constant temperature and humidity chamber at a temperature of 40°C and a humidity of 80% RH for 10 minutes.
[0305] ④After 10 minutes, take the culture dish out of the constant temperature and humidity chamber, turn it over on the prepared A4 paper, and let it stand for 5 minutes.
[0306] ⑤ After 5 minutes, measure the weight of the superabsorbent polymer sample falling on the A4 paper (S 1 ) and the weight of the culture dish at this time (S 2 ), and then the anti-caking efficiency was calculated by the following equation 4. In this case, the obtained value was rounded to one decimal place.
[0307] [Equation 4]
[0308]
[0309] In equation 4,
[0310] W 5 is the weight (g) of a petri dish with a diameter of 90 mm and a height of 15 mm,
[0311] S 1 The weight is W 5 2±0.01 g of the superabsorbent polymer sample is uniformly applied to a culture dish, the culture dish with the sample applied is placed in a constant temperature and humidity chamber set at 40° C. and 80% RH for 10 minutes, it is taken out, turned over on an A4 paper, and then left for 5 minutes, and then the weight (g) of the superabsorbent polymer sample dropped on the A4 paper is measured, and
[0312] S 2 is the measurement S 1 The weight of the culture dish at .
[0313]
Table 1
[0314]
[0315] 1) Parts by weight based on 100 parts by weight of hydrogel polymer
[0316] 2) Parts by weight based on 100 parts by weight of base resin
[0317] 3) Mesh (#20-30): particle size 600-850μm, mesh (#30-50): particle size 300-600μm, mesh (#50-100): particle size 150-300μm
[0318] Referring to Table 1, it was confirmed that the super absorbent polymer of Example 1 prepared by coarse pulverization after adding a carboxylic acid additive to the hydrogel polymer polymerized in the presence of an encapsulated foaming agent, improved both permeability and anti-caking efficiency without reducing the absorption rate, while having similar absorption properties, compared with the super absorbent polymer of Comparative Example 1 prepared without adding such additives during coarse pulverization. Therefore, it was confirmed that the permeability and anti-caking efficiency of the super absorbent polymer can be improved without using an inorganic material such as aluminum sulfate that is generally added during surface cross-linking.
[0319] In addition, in the case of the superabsorbent polymers of Examples 2 to 4 prepared by adding a carboxylic acid additive and then coarsely pulverizing and then adding a small amount of an inorganic material (e.g., aluminum sulfate) in the surface treatment step, even if the absorption rate is slightly reduced, the permeability and anti-caking efficiency can be further improved. Therefore, the content of the inorganic material can be adjusted according to the purpose of the final application of the superabsorbent polymer, so that physical properties suitable for the purpose can be achieved.
Claims
1. A method for preparing a superabsorbent polymer, the method comprising: Step 1: forming a hydrogel polymer by cross-linking and polymerizing a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups in the presence of an internal cross-linking agent, an encapsulated foaming agent, and a polymerization initiator; Step 2: After mixing the hydrogel polymer with the carboxylic acid additive, coarsely crushing the hydrogel polymer; Step 3: Drying and pulverizing the roughly pulverized hydrogel polymer to prepare a powdered base resin; and Step 4: In the presence of a surface crosslinking agent, further crosslinking the surface of the base resin to form a surface crosslinking layer, The carboxylic acid additive is at least one selected from the group consisting of carboxylic acids and salts thereof represented by the following Chemical Formula 1: [Chemical formula 1] In chemical formula 1, A is a C5 to C21 alkyl group, B1 is -OC(=O)-, -C(=O)-O- or -C(=O)-O-CH(R1)-C(=O)-O-, B2 is -CH2-, -CH2CH2-, -CH(R2)-, -CH=CH- or -C≡C-, wherein R1 and R2 are each independently C1 to C4 alkyl, n is an integer from 1 to 3, and C is a carboxyl group.
2. The method for preparing a superabsorbent polymer according to claim 1, in, The encapsulated foaming agent has a structure including a core including hydrocarbon and a shell formed of a thermoplastic resin surrounding the core.
3. The method for preparing a superabsorbent polymer according to claim 2, in, The hydrocarbon is at least one selected from the group consisting of n-propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane, n-hexane, isohexane, cyclohexane, n-heptane, isoheptane, cycloheptane, n-octane, isooctane and cyclooctane, and The thermoplastic resin is a polymer formed of at least one monomer selected from the group consisting of (meth)acrylate compounds, (meth)acrylonitrile compounds, aromatic vinyl compounds, vinyl acetate compounds, and halogenated vinyl compounds.
4. The method for preparing a superabsorbent polymer according to claim 1, in, The encapsulated foaming agent has an average diameter of 5 μm to 30 μm before expansion, and a maximum expansion rate in air of 5 to 15 times.
5. The method for preparing a superabsorbent polymer according to claim 1, in, The encapsulated foaming agent is used in an amount of 0.005 to 1 part by weight relative to 100 parts by weight of the water-soluble ethylenically unsaturated monomer.
6. The method for preparing a superabsorbent polymer according to claim 1, in, In Chemical Formula 1, A is -C6H 13 , -C 11 H 23 , -C 12 H 25 , -C 17 H 35 or -C 18 H 37 .
7. The method for preparing a superabsorbent polymer according to claim 1, in, In Chemical Formula 1, B1 is where * is the bonding site to the neighboring atom.
8. The method for preparing a superabsorbent polymer according to claim 1, in, In Chemical Formula 1, B2 is where * is the bonding site to the neighboring atom.
9. The method for preparing a superabsorbent polymer according to claim 1, in, The carboxylic acid additive is at least one selected from the group consisting of a carboxylic acid represented by Chemical Formula 1, an alkali metal salt thereof, and an alkaline earth metal salt thereof.
10. The method for preparing a superabsorbent polymer according to claim 1, in, The carboxylic acid additive is any one of the compounds represented by the following chemical formulas 1-1 to 1-7:
11. The method for preparing a superabsorbent polymer according to claim 1, in, The carboxylic acid additive is used in an amount of 0.01 to 1.0 parts by weight based on 100 parts by weight of the hydrogel polymer.
12. The method for preparing a superabsorbent polymer according to claim 1, In step 4, at least one inorganic material selected from the group consisting of silica, clay, alumina, a silica-alumina composite, titanium dioxide, zinc oxide and aluminum sulfate is further added together with the surface cross-linking agent.
13. The method for preparing a superabsorbent polymer according to claim 12, in, The inorganic material is used in an amount of 0.001 to 0.3 parts by weight based on 100 parts by weight of the base resin.
14. The method for preparing a superabsorbent polymer according to claim 1, in, The permeability of the prepared superabsorbent polymer measured according to the following equation 3 is 40 seconds or less, and Vortex time at 24 °C is less than 30 seconds: [Equation 3] Permeability (seconds) = T1-B In equation 3, T1 is the time taken for the liquid level to drop from 40 mL to 20 mL after adding 0.2 ± 0.0005 g of superabsorbent polymer sample graded from 30# to 50# to the chromatographic tube, adding saline to make the volume of the saline 50 mL, and standing for 30 minutes. B is the time taken for the liquid level to drop from 40 mL to 20 mL in a chromatographic tube filled with saline.
15. The method for preparing a superabsorbent polymer according to claim 1, in, The anti-blocking (A / C) efficiency of the prepared superabsorbent polymer calculated by the following equation 4 is 50% or more: [Equation 4] In equation 4, W5 is the weight (g) of a culture dish with a diameter of 90 mm and a height of 15 mm, 2±0.01 g of a superabsorbent polymer sample is uniformly applied to a culture dish weighing W5, the culture dish with the sample applied is placed in a constant temperature and humidity chamber set at 40°C and 80% RH for 10 minutes, taken out, turned over on an A4 paper, and then placed for 5 minutes. The weight (g) of the superabsorbent polymer sample falling on the A4 paper is S1, and S2 is the weight of the culture dish when S1 was measured (g).
Citation Information
Patent Citations
Skin care compositions and methods of use thereof
CA2749750A1
Preparation method of super absorbent polymer
CN111819230A